Answer:
B. 1/3 multiplied by k=7
Step-by-step explanation:
7 ÷ ⅓ = k
Multiply both sides by ⅓
7 ÷ ⅓ × ⅓ = k × ⅓
7 = k × ⅓
Factor the numerator and denominator and cancel the common factors.
4x^4 - 2
Answer:
13x10^15
Step-by-step explanation:
8+5 = 13
6+9 = 15
Answer: I am really good at math so if you need help just say so
2(x)^2 - 2(x) - 12 = ?
2(x)^2 - 2(x) - 12
(x)^2 - 6 - x
Multiply ↪1 (-6) = -6
1 + -6 = -5 , right?
-3 + 2 = -1, right?
After we have pulled out the like terms we have to add/subtract! x(x) - 3
Search for the common denominator
2(x) - 3
You can add up 4 for your terms
x + 2 (x - 3)
Make sure you solve this↪ 2 = 0
x + 2 = ?
x + 2 = 0
We have found the first; x = -2
~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~
Since, this one has a single variable, I'll make the step easier and quicker
Solve this part ↪ x-3 = 0
If we had the number 3 to your sides we would have found the outcome of the next x
So, the second x is 3
So, therefore your answer would have to be x =-2 ; x = 3 (most likely option C.)